Some Experiences of an Irish R.M. - Somerville, E. Oe. (Edith Oenone), 1858-1949; Ross, Martin, 1862-1915 (Salt Lake City, UT : Project Gutenberg, 2011)
"Some Experiences of an Irish R.M." by E. Œ. Somerville and Martin Ross is a novel written in the late 19th century. The story unfolds from the perspective of Major Sinclair Yeates, a recently appointed resident magistrate in the rural South-West of Ireland. The narrative primarily explores his humorous and often chaotic experiences as he navigates local politics, eccentric characters, and the challenges of his new role, all set against the backdrop of a vividly depicted Irish landscape. The opening of the novel introduces Major Yeates as he reflects on his recent appointment and the difficulties he faces settling into his new home at Shreelane. He finds himself overwhelmed by the dilapidated condition of the house, the peculiarities of his landlord Mr. Knox, and the antics of the local inhabitants. Yeates grapples with practical challenges of household life while simultaneously facing ghostly legends associated with his predecessor, Great-Uncle McCarthy. The tone is set for a series of comedic misadventures as Yeates becomes embroiled in the quirks and oddities of rural Ireland, hinting at the humorous yet poignant moments that characterize his life as a resident magistrate. (This is an automatically generated summary.)
Great-Uncle McCarthy -- In the Curranhilty country -- Trinket's colt -- The waters of strife -- Lisheen races, second-hand -- Philippa's fox-hunt -- A misdeal -- The holy island -- The policy of the closed door -- The house of Fahy -- Occasional licenses -- "Oh love! Oh fire!"
Release date is 2011-01-15
Al Haines
Keywords: Humorous stories, English; Ireland -- Social life and customs -- Fiction; British -- Ireland -- Fiction; Justices of the peace -- Fiction